ECONOMIC GROWTH IN SHARIA BANKING TIME: PERTUMBUHAN EKONOMI PERBANKAN SYARIAH WAKTU - Aldiansyah (UPMI Proceeding Series, 2023)
Human resources in an organization determine the success and goals that can be achieved. Therefore, all questions related to personnel, which also includes the management of employee information must act properly, correctly and transparently. So that employee information can be obtained properly by all parties who need it for every need. The development of computerized technology also supports the smooth flow of information and communication related to personnel information at the Medan Religious Education and Training Center. Thus, information services can be implemented in such a way that problems that arise can be resolved and the quality of the activities of educators and education staff can be improved, so that their task is to facilitate the process of inputting employee data. The conclusion of the creation of this system is that this system can facilitate data processing, this system is also easy to understand, learn and use